The Influence of Entrepreneurial Orientation and Innovation Capability on Perceived Firm Performance with The Mediating Role of Market Orientation: Case study in PT WIKA Industri & Konstruksi - Anggiat Maju Lubis; Firdaus Basbeth (Sekolah Tinggi Manajemen IPMI, 2021)
Performance of PT WIKON in two consecutive years indicated run into downtrend from the year 2018 to the year 2019. Low levels of Entrepreneurial Orientation, Innovation Capability, and Market Orientation have been suspected as factors leading to the performance of PT WIKA Industri & Konstruksi. The objective of this study is to investigate Market Orientation as the mediator of relationship Entrepreneurial Orientation and Innovation Capability on Firm Performance in a construction company. However, study-related Market Orientation as a mediator on the indirect effect of Innovation Capability and Firm Performance is still rare, therefore research on this subject can be seen as Novelty. There are Six theory-based hypotheses are measured. This research employs a quantitative approach with empirical evidence of employees and BOD of PT WIKA Industri & Konstruksi. Survey data are from 93 respondents were analyzed used structural equation modeling (SEM). The findings of this research showed that Market Orientation has a positive effect on Firm Performance. Surprisingly, Entrepreneurial Orientation (EO) and Innovation Capability (IC) independently do not have a direct effect on Firm Performance. The Effect of Entrepreneurial Orientation (EO) on Firm Performance (FP) is mediated by Market Orientation. Likewise, the effect of Innovation Capability (IC) on Firm Performance (FP) is mediated by Market Orientation. These results suggest that Entrepreneurial Orientation and Innovation Capability should focus on Market Orientation to improve the overall Firm Performance. Besides, it is highly recommended to middle management and above of PT WIKA Industri & Konstruksi should focus and allocate resources to Market Orientation to improve their Firm Performance.